2020
DOI: 10.1097/hco.0000000000000790
|View full text |Cite
|
Sign up to set email alerts
|

Management of renovascular hypertension

Abstract: Purpose of review Renovascular occlusive disease remains a common cause of resistant and rapidly progressive hypertension. The present review summarizes current practice regarding management of renovascular hypertension (RVH). Recent findings Current data using blood oxygen level dependent MR emphasize the tolerance of the kidney to moderate reductions in blood flow and the efficacy of antihypertensive drug therapy for many individuals. Prospective tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Medications used in RVHT angiotensin-converting enzyme inhibitor (ACEI)/ARB are the best options to start with. It showed an improvement in the survival rate [ 13 ]. Although ARB decreases the glomerular filtration rate (GFR) initially, it does not cause a long-term loss in renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medications used in RVHT angiotensin-converting enzyme inhibitor (ACEI)/ARB are the best options to start with. It showed an improvement in the survival rate [ 13 ]. Although ARB decreases the glomerular filtration rate (GFR) initially, it does not cause a long-term loss in renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Renal revascularization endovascular or open are the surgical treatment method used in RVHT, with a preference for the endovascular method. Young aged patients with the non-atherosclerotic renovascular disease and others are among the factors favoring renal revascularization over medical treatment [ 13 ]. Despite the use of renal revascularization and surgery in the management of renal artery compression, they are associated with surgical complications and stent complications, and it has to be individualized.…”
Section: Discussionmentioning
confidence: 99%
“…ARAS prevalence ranges from 30% among patients with coronary artery disease to 50% in elderly patients or in those with atherosclerotic lesions in different vascular territories. [1][2][3] Several reports have emphasized the common association of ARAS with documented CAD, and studies based on series of clinically selected groups indicated the prevalence of ARAS at 11% to 18%. [1][2][3] In the studies of Weber -Mzell et al 9 and Harding et al 11 performed in the cohorts of patients undergoing cardiac catheterization for suspected CAD, ARAS (defined as renal artery stenosis >50%) was found in 10.7% and 11% of patients, respectively.…”
Section: Atherosclerotic Renal Artery Stenosis and Cardiovascular Dis...mentioning
confidence: 99%
“…[1][2][3] Several reports have emphasized the common association of ARAS with documented CAD, and studies based on series of clinically selected groups indicated the prevalence of ARAS at 11% to 18%. [1][2][3] In the studies of Weber -Mzell et al 9 and Harding et al 11 performed in the cohorts of patients undergoing cardiac catheterization for suspected CAD, ARAS (defined as renal artery stenosis >50%) was found in 10.7% and 11% of patients, respectively. In the study by Rihal et al, 12 which included 297 individuals who underwent coronary angiography, RAS of 50% or more was found in 9.2% of patients.…”
Section: Atherosclerotic Renal Artery Stenosis and Cardiovascular Dis...mentioning
confidence: 99%
See 1 more Smart Citation